Cancer Incidence Among Hardmetal Production Workers: The Swedish Cohort. Issue 12 (December 2017) - Svartengren, Magnus; Bryngelsson, Ing-Liss; Marsh, Gary; Buchanich, Jeanine; Zimmerman, Sarah; Kennedy, Kathleen; Esmen, Nurtan; Westberg, Håkan
Abstract : N/A: The cancer incidence was determined for 3713 workers from three plants from 1958 to 2011. The exposure measures were ever/never exposed, duration, cumulative, and mean cobalt concentrations. The incidence of all malignant neoplasms was increased at one plant, but standardized incidence ratio (SIR) was 0.96 for all workers. Lung cancer incidence was increased for all workers, SIR 1.38 (1.01 to 1.85). The lung cancer incidence was associated with shorter employment time and showed no exposure–response. There was decreased incidence for skin cancer. Increased lip cancer incidence found at one of the production plants might be related to diagnostic intensity. Lung cancer incidence showed no correlation to cobalt exposure based on internal comparison. The increased SIR for all workers might be associated with other factors.